Philanthropy in British and American fiction Dickens, Hawthorne, Eliot, and Howells - Christianson, Frank (Edinburgh University Press, 2007)
Explores the relationship between philanthropy and literary realism in novels by Charles Dickens Nathaniel Hawthorne George Eliot and William Dean Howells and examines how each used the figure of philanthropy both to redefine the sentiments that informed social identity and to refashion their own aesthetic practices